EARLY PREGNANCY DIAGNOSIS IN CORRIEDALE SHEEP BY REALTIME B-MODE ULTRASONOGRAPHY - GANAIE, B A; KHAN, M Z; MAKHDOOMI, D M; ISLAM, R; WANI, G M (The Indian Journal of Animal Reproduction, 2023)
Fifty Corriedale ewes were scanned in dorsal recumbency for pregnancy diagnosis using realtime B-mode ultrasonic equipment provided with a 3.5 MHz sector array transducer at 15 days interval starting from 15 days post tupping upto lambing through trans-abdominal approach. The accuracy, sensitivity, specificity and the prediction values of the technique were evaluated at the different stages of gestation, by comparing the ultrasonic results with lambing records and noticeable abortions. An accuracy of 68% and a sensitivity of 70A% were observed at Day 27 .0 ± 0.83 ( 15-30), which increased significantly (P<0.05) to 100% at day63.2 ± 0.75 (day 61-75) of gestation. It was found that presence of echoic embryo within an anechoic fetal fluid, fetal cardiac activity, placentomes and developing fetal skeleton were the reliable indicators of pregnancy.